Wide-gamut lasing from a single organic chromophore. Issue 1 (December 2018) - Lane, S.; Vagin, S.; Wang, H.; Heinz, W.; Morrish, W.; Zhao, Y.; Rieger, B.; Meldrum, A.
Abstract The development of wideband lasing media has deep implications for imaging, sensing, and display technologies. We show that a single chromophore can be engineered to feature wide-gamut fluorescence and lasing throughout the entire visible spectrum and beyond. This exceptional color tuning demonstrates a chemically controlled paradigm for light emission applications with precise color management. Achieving such extensive color control requires a molecular blueprint that yields a high quantum efficiency and a high solubility in a wide variety of liquids and solids while featuring a heterocyclic structure with good steric access to the lone pair electrons. With these requirements in mind, we designed a lasing chromophore that encloses a lasing color space twice as large as the sRGB benchmark. This record degree of color tuning can in principle be adapted to the solid state by incorporating the chromophore into polymer films. By appropriately engineering the base molecular structure, the widest range of lasing wavelengths observed for a conventional gain medium can be achieved, in turn establishing a possible route toward high-efficiency light emitters and lasers with near-perfect chromaticity. Controllable chromophores for multicolored light emission A molecule capable of fluorescence and lasing over multiple wavelengths in the visible spectrum and beyond could have applications from sensors and biomarkers to holographic projectors. Organic molecules called chromophores determine which frequencies of light are absorbed and emitted, thus defining a molecule's color. Alkiviathes Meldrum at the University of Alberta in Edmonton, Canada, and co-workers have engineered a chromophore that emits different colors of light depending on which chemical it is placed in. The team carefully manipulated the base structure of the chromophore to ensure it was soluble and had a wide emission band. In one solvent the chromophore emitted red light, while in another the fluorescence was deep blue. Other chemicals resulted in many other colors, all emitted from a single chromophore. Their design could lead to new types of tunable lasers.